Improving Students' Problem Solving Ability and Mathematical Communication through the Application of Problem Based Learning - Nufus, Hayatun; Mursalin, M (Electronic Journal of Education, Social Economics and Technology, 2020)
The purpose of this study was to determine the improvement of students' mathematical problem solving and communication skills using problem-based learning better than ordinary learning; to determine the interaction between learning and early mathematical abilities to increase students' mathematical problem solving and communication skills; to find out how the process of answers made by students in solving problems in problem-based learning and ordinary learning. This type of research is quasi-experimental. The population in this study were all grade VII students of SMP Lhokseumawe who were accredited and the samples were randomly selected, namely: SMPN 10 consisted of class VII-4 (experimental class) and class VII-2 (control class), SMPN 11 Lhokseumawe consisted of class VII- 3 (experimental class) and class VII-1 (control class). Data analysis was performed using two-way ANOVA. The results of this study indicate that there is an increase in the problem-solving ability and mathematical communication of students using problem-based learning better than students who receive regular learning; there is no interaction between learning and the level of students 'ability to increase students' problem-solving abilities and mathematical communication; the process of solving the problem of students' answers to learning using problem-based learning is better than ordinary learning.